Colombiathelphusa, a new genus of freshwater crab from Colombia, and the first location record of Eidocamptophallus chacei (Pretzmann, 1967) (Crustacea: Decapoda: Pseudothelphusidae) - Campos, Martha R.; Magalhães, Célio (Zootaxa, 2014)
A new genus of pseudothelphusid crab, Colombiathelphusa gen. nov., is established to include Colombiathelphusa culmarcuata n. sp., from the Chocó Department, western Colombia. The new genus is characterized by the morphology of the male first gonopod, which has a prominent lateral process, a cephalic surface with two spine-like cephalic processes subdistally, and the outline of the apex strongly recurved, resembling a bow’s arch. The new species is described and illustrated. The first location record of Eidocamptophallus chacei (Pretzmann, 1967), is made and its male first gonopod is redescribed and illustrated. Possible affinities of both taxa are discussed.